Ghostly Collaboration: the Authorship of False Criminal Confession - Mary Laughlin (Authorship, 2014)
Drawing on a body of confession scholarship, “Ghostly Collaboration” defines “coercive ghostwriting,” an authorship-inspired term for collaborative practices enacted between custodial criminal suspects and professional police interrogators resulting in coerced, potentially false confession. Within the United States, still-prominent notions of a Romantically-influenced autonomous Author problematically intersect with public perception of collaborative texts; the coercive ghostwriting label is intended to draw explicit attention to co-authorship via coercive collaboration, hopefully contributing to the ongoing efforts of researchers working to challenge inaccurate views of false confessions.